Reactivation of hepatitis B virus in patients with undetectable HBsAg undergoing chemotherapy for malignant lymphoma or multiple myeloma. Issue 11 (7th August 2013) - Matsui, Takeshi; Kang, Jong‐Hon; Nojima, Masanori; Tomonari, Akiko; Aoki, Hironori; Yamazaki, Hajime; Yane, Kei; Tsuji, Kunihiko; Andoh, Seisho; Andoh, Sachiko; Sakai, Hajime; Maemori, Masayo; et al.
ABSTRACT Despite increasing reports of hepatitis B virus (HBV) reactivation in hematological malignancies, its incidence, and risk factors are still obscure. The aim of this study was to clarify the frequency and risk factors of HBV reactivation in hepatitis B surface antigen (HBsAg) undetectable patients with malignant lymphoma or multiple myeloma, during or after chemotherapy. A total of 109 patients with undetectable HBsAg undergoing chemotherapy for malignant lymphoma or multiple myeloma were enrolled in this study. Anti‐hepatitis B surface (anti‐HBs) and anti‐hepatitis B core (anti‐HBc) were checked before treatment, and HBV DNA in sera was quantified monthly during and after chemotherapy. Out of 109 patients, 42 (38.5%) had anti‐HBs and 59 (54.1%) had anti‐HBc. Among the 59 anti‐HBc positive patients, four patients (4/59, 6.8%) showed HBV reactivation during 20.5 median follow‐up months. In all four patients with HBV reactivation, peripheral lymphocyte counts before chemotherapy were lower than those without HBV reactivation (P = 0.033). HBV reactivation occurred during and after chemotherapy containing rituximab for non‐Hodgkin lymphoma. Four patients, who had HBV reactivation, did not develop de novo hepatitis due to HBV reactivation and were able to undergo chemotherapy against malignant lymphoma as scheduled. Monitoring of HBV DNA in sera is useful for the early diagnosis of HBV reactivation, and preemptive therapy is an useful alternative to prevent hepatitis due to HBV reactivation. Patients must be monitored periodically for HBV‐DNA levels during and after chemotherapy. J Med. Virol. 85:1900–1906, 2013. © 2013 Wiley Periodicals, Inc.